2019
DOI: 10.12659/msm.915678
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Polymorphisms Associated with Susceptibility to Obesity: A Meta-Analysis

Abstract: BackgroundObesity has become a global public health problem. Obesity increases the risk of several lethal diseases. This study aimed to assess whether the obesity susceptibility was associated with genetic variation in vitamin D receptor (VDR) gene by conducting a meta-analysis.Material/MethodsPubMed, EMBASE and Cochrane Library databases were screened for all relevant articles published up to October 2018. The pooled odds ratios (OR) were calculated using STATA 13.0 software for 4 polymorphisms in the VDR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Another meta-analysis by Zeng et al [62] confirmed that the BsmI (rs739837) SNP was associated with GDM, and Wang et al [82] confirmed that the FokI SNP may confer susceptibility to GDM. In addition, meta-analysis studies have documented other human diseases, such as T2DM [63], obesity [83], CVD [84], and polycystic ovary syndrome (PCOS) [85], which are all risk factors for GDM and showed associations with specific SNPs in the VDR gene [63,[83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis by Zeng et al [62] confirmed that the BsmI (rs739837) SNP was associated with GDM, and Wang et al [82] confirmed that the FokI SNP may confer susceptibility to GDM. In addition, meta-analysis studies have documented other human diseases, such as T2DM [63], obesity [83], CVD [84], and polycystic ovary syndrome (PCOS) [85], which are all risk factors for GDM and showed associations with specific SNPs in the VDR gene [63,[83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mirzazadeh et al reported the prevalence of obesity as 13.7% in men and as 27.3% in women (9). VDR gene polymorphisms have been frequently found to be related to obesity, although these findings differ by population (10)(11)(12).…”
Section: Conclusiónmentioning
confidence: 99%
“…Mirzazadeh, et al ., have reported an obesity prevalence of 13.7% in men and 27.3% in women 9 . Frequently, VDR gene polymorphisms have been found to be related to obesity, although these findings differ depending on the population 10 - 12 . Considering them as risk factors for obesity, we studied three of these polymorphisms: Taq I, Apa I, and Bsm I, and their relationships with serum factors in an obese Iranian population.…”
mentioning
confidence: 99%